Menuju Cita Supremasi Hukum - Khumarga, Dahnial (LAW REVIEW, 2003)
Supremacy of Law, which means that all persons (individuals and government) are subject to laws. Supremacy of the law requires the rule of law. Aristoteles said more than two thousand years ago: " The rule of law is better that of any individual". Lord Chief Justice Coke quoting Bracton said in the case of Proclamation (1610) 77 ER 1352:  " The King himself ought not to be subject to man, but subject to God and the Law,  because the law makes him King". fHTTP://www.ourcivilisation.com /cooray/btof/  chapl80.htm). The rule of law ensures that individuals have a secure area of autonomy and have settled expectations by having their rights and duties pre-establish ed and enforced law. The rules of proceduring, evidance and natural justice also protect individuals from arbitracy governmental action and illegal deprivation of private rights. They are essential to the protection of individual right of personal freedom and private property.